Security assessment of FTMSK web server / Md Nazri Hashim - Hashim, Md Nazri (2005)
Exploitation by attackers whose have breached the network security of some of the world's most vulnerable institutions and organization had become increased every year including in FTMSK web server, University Technology of MARA (UiTM). Within this type of attention, network security has gone from the as an extra services to the main services in a relatively short period in FTMSK web server. The main purpose is to mitigate security risk and assure that their FTMSK digital assets, especially FTMSK websites and mail server, are in safe and digital environment is become a better condition to the staff and the students. Auditing activities can help to identify the weakness and vulnerabilities in the FTMSK web server at FTMSK to prevent he attacks against it by the hackers or crackers. This idea is, find, identify and fix these weakness or vulnerabilities before the attackers use them against FTMSK computer network system.